Metabolomics and Microbiomics Reveal Impacts of Rhizosphere Metabolites on Alfalfa Continuous Cropping - Ruiting Wang; Jinxin Liu; Wanyi Jiang; Pingsheng Ji; Yonggang Li (Frontiers in Microbiology, 2022)
Alfalfa long-term continuous cropping (CC) can pose a serious threat to alfalfa production. However, the mechanism of alfalfa CC obstacle is unclear as of today. Our preliminary study showed that the main factors of CC obstacle were not the lack of nutrients or water in alfalfa rhizosphere soils. Further, we evaluated physic-chemical property, microbial population structure, and metabolite differences of alfalfa rhizosphere soils with CC for 1, 7, and 14 years based on analysis of metabolomics and microbiomics. Four phenolic acid metabolites, including p-coumaric acid, ferulic acid, vanillic acid, and p-hydroxybenzoic acid, were found to have significant differences among different CC years, which may be the key factors of CC obstacle. Among them, p-coumaric acid and ferulic acid could significantly decrease the germination rate of alfalfa seeds by 21.11 and 16.67% at the concentration of 100 μg/mL and the height (root length) of alfalfa seedlings by 21% (32.9%) and 13.72% (16.45%). Moreover, these metabolites could effectively promote the growth of some pathogenic fungi, causing alfalfa root rot. Among them, p-coumaric acid obviously and significantly aggravated the occurrence of alfalfa root rot. With the increase of CC years, soil microbial community changed from fungi to bacteria; fungi decreased by 10.83%, fungi increased by 8.08%, and beneficial microorganisms decreased with the increase of CC years. Field analysis and experimental verification showed that the above results were consistent with that of CC obstacle in the field. Among the key metabolites, the autotoxicity of p-coumaric acid was the strongest. This study fully proved that the continuous accumulation of autotoxic substances in alfalfa rhizosphere was the key factor causing alfalfa CC obstacles.